Investigating the Pathogenesis of Severe Malaria: A Multidisciplinary and Cross-Geographical Approach - Wassmer, Samuel C. (Am J Trop Med Hyg, 2015)
More than a century after the discovery of Plasmodium spp. parasites, the pathogenesis of severe malaria is still not well understood. The majority of malaria cases are caused by Plasmodium falciparum and Plasmodium vivax, which differ in virulence, red blood cell tropism, cytoadhesion of infected erythrocytes, and dormant liver hypnozoite stages. Cerebral malaria coma is one of the most severe manifestations of P. falciparum infection. Insights into its complex pathophysiology are emerging through a combination of autopsy, neuroimaging, parasite binding, and endothelial characterizations. Nevertheless, important questions remain regarding why some patients develop life-threatening conditions while the majority of P. falciparum-infected individuals do not, and why clinical presentations differ between children and adults. For P. vivax, there is renewed recognition of severe malaria, but an understanding of the factors influencing disease severity is limited and remains an important research topic. Shedding light on the underlying disease mechanisms will be necessary to implement effective diagnostic tools for identifying and classifying severe malaria syndromes and developing new therapeutic approaches for severe disease. This review highlights progress and outstanding questions in severe malaria pathophysiology and summarizes key areas of pathogenesis research within the International Centers of Excellence for Malaria Research program.